THE STUDY OF THE MACRO- AND MICROELEMENT COMPOSITION IN LEAVES AND SEEDS OF NITREBUSH (NITRARIA SP) BY ICP-MS METHOD (Scientific journal of the Fergana State University, 2024)
Samples of leaves and seeds from nitrebush plants growing in the Yazyavan-Koshtepa region were analyzed by inductively coupled plasma mass spectrometry. The qualitative and quantitative content of 31 different elements was determined in these plant samples. Out of these identified elements, five are macronutrients, twenty-four are trace elements, and two are toxic elements.  The amount of elements such as calcium, phosphorus,  potassium,  magnesium,  sodium, iron, strontium, aluminum, copper, zinc, chromium, manganese, titanium, silver, and rubidium in the studied parts of nitrebush plants was determined. The highest values for these elements were found in the leaves, with sodium having the highest concentration and the seeds had the highest amount of potassium. Two highest elements, sodium and potassium accounting for 84.7% of the total macronutrient content. Seeds contain more potassium (10.07 mg/g), sodium (7.8 mg/g) as macronutrients, and aluminum (104 µg/g) as a trace element. Poisonous elements such as arsenic and cadmium were also found in the plant samples.